1992
DOI: 10.1007/bf00911238
|View full text |Cite
|
Sign up to set email alerts
|

Negative cognitive errors and positive illusions for negative divorce events: Predictors of children's psychological adjustment

Abstract: This study examined the relations among negative cognitive errors regarding hypothetical negative divorce events, positive illusions about those same events, actual divorce events, and psychological adjustment in 38 8- to 12-year-old children whose parents had divorced within the previous 2 years. Children's scores on a scale of negative cognitive errors (catastrophizing, overgeneralizing, and personalizing) correlated significantly with self-reported symptoms of anxiety and self-esteem, and with maternal repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 68 publications
0
27
0
Order By: Relevance
“…The Thoughts about Parenting Situations Scale was written in the tradition of social cognitive research that has measured children's and adults' general attribution style (Henriques & Leitenberg, 2002;Leitenberg, Yost, & Carroll-Wilson, 1986;Seligman et al, 1984), appraisals of divorce-related stressors (Mazur et al, 1992(Mazur et al, , 1999 and social problem-solving (e.g., Spivack & Shure, 1974) using hypothetical events. For the present study, I assessed parents' appraisals of hypothetical rather than actual events because of the focus on cognitive styles; hypothetical situations allowed the presentation of stock stimulus cues for which all participants could endorse negatively or positively biased appraisals.…”
Section: Thoughts About Parenting Situationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Thoughts about Parenting Situations Scale was written in the tradition of social cognitive research that has measured children's and adults' general attribution style (Henriques & Leitenberg, 2002;Leitenberg, Yost, & Carroll-Wilson, 1986;Seligman et al, 1984), appraisals of divorce-related stressors (Mazur et al, 1992(Mazur et al, , 1999 and social problem-solving (e.g., Spivack & Shure, 1974) using hypothetical events. For the present study, I assessed parents' appraisals of hypothetical rather than actual events because of the focus on cognitive styles; hypothetical situations allowed the presentation of stock stimulus cues for which all participants could endorse negatively or positively biased appraisals.…”
Section: Thoughts About Parenting Situationsmentioning
confidence: 99%
“…Although the cognitive-behavioral model of stress has generated extensive research, and family researchers (Crnic & Booth, 1991;Crnic & Greenberg, 1990;Sigel, 1985) have emphasized the importance of examining the influence of parental perceptions on family development, research on negative cognitive errors and positive illusions in family relationships has been limited to children's appraisals in divorce situations (Krantz, Clark, Pruyn, & Usher, 1985;Mazur, Wolchik, & Sandler, 1992;Mazur, Wolchik, Virdin, Sandler, & West, 1999). The influence of parents' negatively and positively biased appraisals on psychological and parenting adjustment has never been examined, although such research could offer insight into the more and less effective ways that parents cope with daily parenting stressors.…”
Section: Introductionmentioning
confidence: 99%
“…An important future direction would be to examine the predictive utility of the IEGS in relation to other dimensions of psychopathology as well. Because previous research has shown that cognitive errors about perceived responsibility correlate with anxiety, eating disorders, and poor coping (Epkins 1996; Leitenberg et al 1986; Mazur et al 1992; Ostrander et al 1995; Weems et al 2001), we would expect the IEGS to be useful in the prediction of a variety of child and adolescent disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Leitenberg and colleagues also focused on these kinds of cognitive error. Using the Children’s Negative Cognitive Error Questionnaire, they (and others) found that such cognitive errors were correlated with depression, low self-esteem, anxiety, eating disorders, and poor coping with divorce (Leitenberg et al 1986; see also Epkins 1996; Mazur et al 1992; Ostrander et al 1995; Weems et al 2001). Based on this work, we define the inappropriate aspect of guilt as the negative cognitions associated with the erroneous assumption of responsibility and the excessive aspect of guilt as the disproportionate negative affect in response to a mishap for which one has assumed such responsibility.…”
mentioning
confidence: 99%
“…Research has documented the existence of positive illusions in typical and atypical child populations (e.g., Falbo, Poston, Triscari, & Zhang, 1997;Heath & Glen, 2005;Hoza et al 2004;Mazur, Wolchik, & Sandler, 1992), but it could be argued that members of these populations are not cognitively mature enough to adequately appraise their abilities, or that these populations are somehow qualitatively different. For example, Owens, Goldfine, Evangelista, Hoza, and Kaiser (2007) stated that children with ADHD are cognitively unique and that the way they endorse positive illusions is different from other children.…”
Section: Objective 3: the Relationship Between Positive Illusions Andmentioning
confidence: 99%